Anaplastic thyroid cancer: current capabilities of an oncologist - A. L. Pylev; D. S. Romanov; N. V. Lasunin; D. A. Balaeva; M. P. Kazakov (Опухоли головы и шеи)
Continuous development of oncology as a science in the last decades and years led to noticeable improvement in treatment outcomes for patients with various malignant tumors. Diagnostics, surgery, radiotherapy significantly contributed to this improvement, however they cannot be compared to the progress achieved through advancements in our knowledge of genetic structure of tumors and subsequent advancements in pharmacology which allowed to achieve qualitatively better survival in oncological patients. These advancements did not leave out such a serious and highly lethal, though fortunately rare, disease as anaplastic thyroid cancer. This article is dedicated to the possibilities of using checkpoint inhibitors in treatment of this pathology to increase expected life span of the patients.